2013
DOI: 10.1016/j.tourman.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Why hotel rooms were not full during a hallmark sporting event: The 2009 World Games experience

Abstract: ROC h i g h l i g h t s < Hallmark sporting events may not generate consistent and substantial tourism demand. < Factors contribute to the soft hotel occupancy and revenue intakes during the 2009 World Games are explained. < Displacement effects of visitors and the imbalance power between stakeholders are considered as the major causes. a b s t r a c tHosting mega-and hallmark-events is perceived as an important vehicle for tourism development. However, in the case of the 2009 World Games, the first internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Surprisingly, little research and practice emphasize the influence of exogenous factors on hotel development. Exceptions can be found in studies of specific sources of tourism or festivals, such as those related to skiing, wine, and sports (Chen & Wang, 2014;Nieves & Segarra-Cipr es, 2015;Quintal, Thomas, & Phau, 2015;Song, You, Reisinger, Lee, & Lee, 2014;Sun et al, 2013). These findings spark interest in establishing the connection between the hotel industry and regional development.…”
Section: Factors Influencing Hotel Economic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, little research and practice emphasize the influence of exogenous factors on hotel development. Exceptions can be found in studies of specific sources of tourism or festivals, such as those related to skiing, wine, and sports (Chen & Wang, 2014;Nieves & Segarra-Cipr es, 2015;Quintal, Thomas, & Phau, 2015;Song, You, Reisinger, Lee, & Lee, 2014;Sun et al, 2013). These findings spark interest in establishing the connection between the hotel industry and regional development.…”
Section: Factors Influencing Hotel Economic Performancementioning
confidence: 99%
“…Hotels have different characteristics (Huang, Liu, & Hsu, 2013) that may serve and accommodate customers with differing socioeconomic backgrounds and intentions. Some research has been conducted into particular types of hotels, such as international tourist hotels (Sun, Rodriguez, Wu, & Chuang, 2013) and economy hotels (Huang et al, 2013). However, systematic examinations and comparisons of hotels' determinants in one series (e.g., hotels with star ratings) are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Tourist visitation and place marketing. Events are perceived as an important vehicle for tourism development in terms of adding to the tourism experience, as well as in the longerterm contributing to the place marketing and appeal of a tourist destination (Sun, Rodriguez, Wu, & Chuang, 2013;Weed, 2014). However, economic analysis of the tourism benefits from largescale sport events have highlighted that while these events provide important media and marketing opportunities, they are not without challenges.…”
Section: Study Of Tourism Legacies From the London 2012mentioning
confidence: 99%
“…In terms of hotel development, studies have shown that despite long-term pre-event planning, hotel occupancies can often fall short of expected demand, in turn impacting on the MS 17 077 Event Management E-pub economic gains promoted in event rhetoric (Barreda, Zubieta, Chen, Cassilha, & Kageyama, 2017;Sun et al, 2013). In the case of the 2009 World Games hosted in Taiwan, Sun et al (2013) found a range of factors contributed to lower than expected occupancy rates, including inefficient collaboration between stakeholders, competition from hotels in regional areas, and a perception of an unfriendly local area associated with illness, climatic conditions and political controversies.…”
Section: Ms 17 077 Event Management E-pubmentioning
confidence: 99%
“…Even during peak seasons, only a fraction of hotels face overdemand. Sun, Rodriguez, Wu, and Chuang (2013) state that hosting large-scale, high-profi le sporting events may not lead to the expected volume of hotel occupancies. Using the 2009 World Games that took place in Kaohsiung, Taiwan, from 16 to 26 July, 2009 as a case study, they fi nd that for the month of July 2009, the occupancy rate of Kaohsiung tourism hotels was 64%, and that of general hotels was 47%, which was only 2% and 4% higher than the national average respectively.…”
Section: Introductionmentioning
confidence: 99%